(untitled) (Global Journal of Science Frontier Research, 2013)
Background: Polycystic ovary syndrome (PCOS) is the most common reproductive endocrinopathy and currently considered to be a part of the metabolic syndrome. Women with PCOS cluster risk factors associated with risk of atherosclerosis. These risk factors include insulin resistance, dyslipidemia, hyperandrogenemia, obesity, endothelial dysfunction and oxidative stress. homocysteine and paraoxonase 1 in PCOS in two different regimes of treatment with Metformin and Folic acid in order to elucidate some risk factors that may lead to atherosclerosis and vascular diseases in the corresponding patients. Patients and Methods: Fifty patients with PCOS were enrolled in this study that subdivided into two groups according to type of treatment received i.e. G1 (comprising 25 patients) treated with Metformin only, G2 (comprisin25 patients) with Metformin and Folic acid. Serum Homocysteine (Hcy), Paraoxonase 1(PON1) Apolipoprptein A-1(Apo A-1) and Apolipoprotein B(Apo B) were determind by using enzymelinked immunosorbent assay (ELISA). Reduced Glutathion (GSH) and Malondialdehyde (MDA) were determined by using colorimetric method. Results: The results indicated a significant increase in the serum levels of Hcy(p